Medical Student Procedural Skills Curriculum Handbook and Instructor's Guide - Maura Sullivan; May Nally; Josette Etcheverry; Jennifer Israel; Craig Baker; Kenji Inaba (Association of American Medical Colleges, 2013)
Abstract This module includes a handbook of procedural skills created as part of a school-wide procedural skills curriculum held annually for all Year II medical students prior to the start of the clinical clerkships at the Keck School of Medicine of the University of Southern California. The Delphi method was used to determine which skills were the most important or applicable to all students regardless of specialty choice. The authors excluded skills that were already being taught in the curriculum. The handbook contains the objectives, indications, contraindications, general principles, and procedural steps for each skill. At the end of the 8-hour session, each student is asked to demonstrate the skill to one of the instructors. The instructor subjectively rates whether or not each learner completed the essential tasks of the skill in the correct sequence. A student who does not successfully demonstrate the skill is asked to attend another session. The curriculum was implemented in 2008 and it has been a success. Since that time there have been numerous requests from colleagues at other institutions for the handbook. The biggest challenge in implementing this curriculum is getting the students to practice and perform the skills during the required clerkships. Students have found this process burdensome and have asked for dedicated time to practice each skill. In response to this we have set up an additional animate skills lab adjacent to the student conference room and have educated residents and faculty about the importance of providing the students the opportunity to perform these skills.